Advances in Total Synthesis of Some 2, 3, 5‐Trisubstituted Tetrahydrofuran Natural Products. Issue 18 (25th August 2020) - Fernandes, Rodney A.; Pathare, Ramdas S.; Gorve, Dnyaneshwar A.
Abstract: 2, 3, 5‐Trisubstituted tetrahydrofuran moiety is ubiquitous in natural products. These have served as appealing candidates for total synthesis due to their varied bio‐ and pharmaceutical activities. This tutorial review delineates the ingenious efforts by many researchers in the total synthesis of selected natural products based on a common 2, 3, 5‐trisubstituted tetrahydrofuran core structure. Many of the syntheses display nuanced interplay between new methods and the ingenuity of planned strategies achieved through catalysis or cascade chemistry. In some cases, the chiron approach has come quite handy, wherein the structural features and the stereochemistry in select molecules could map well with naturally available starting materials. This compilation also aims to enhance the diversity space based on these natural products and further interest in sustainable total synthesis. Abstract : The 2, 3, 5‐trisubstituted tetrahydrofuran moiety is encountered in many natural products. Over 38 total syntheses including a few formal syntheses on trans ‐kumausyne, kumausallene, oxylipids, petromyroxol and Hagen's gland lactones with a substituted THF moiety are schematically presented in this review. The syntheses display the tactics involved, the strategic reactions addressing the relative and absolute stereochemistry requirement and other structural features, like the ( E )‐enyne, the chiral allene or the furofuranone moieties that were accomplished efficiently.